Personalizing E-Commerce Experiences: A Machine Learning Framework for Dynamic Gamification and Customer Engagement - Azizul Azman; Mohd Shahrizal Sunar; Muhamad Najib Zamri (Journal of ICT Research and Applications, 2026)
E-commerce platforms are increasingly challenged to sustain customer engagement amidst intensifying competition. Traditional gamification approaches, characterized by static, uniform mechanics, often fail to adapt to individual user preferences, leading to diminishing returns and decreased engagement over time. These conventional methods typically employ fixed reward structures that do not account for individual user behavior, resulting in a lack of sustained engagement. This paper introduces a comprehensive machine learning (ML) framework for dynamic gamification, designed to personalize game elements in real-time based on individual user behavior patterns. The framework integrates clustering algorithms, reinforcement learning (RL), and collaborative filtering techniques to analyze user interactions and generate adaptive gamified experiences. Simulated testing, conducted using a publicly available e-commerce customer behavior dataset from Kaggle, provided insights into diverse user preferences and behaviors. Simulated results demonstrated significant improvements, including a 32% increase in daily active users, a 24% higher conversion rate, and a 30.8% improvement in 30-day customer retention. The framework addresses critical technical challenges, such as scalability, real-time processing, and ethical data usage. This research contributes to the advancement of personalized digital experiences in e-commerce, offering practical guidelines for enhancing customer engagement through AI-driven gamification.